2009
DOI: 10.1002/ar.20917
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the Blood‐Spleen Barrier in the Soft‐Shelled Turtle, Pelodiseus Sinensis

Abstract: We investigated the structure of the soft-shelled turtle, Pelodiseus sinensi, spleen and demonstrated that there were several microanatomical peculiarities by light and transmission electron microscopy. In the spleen, the white pulp of the spleen was composed of two compartments, the periarteriolar lymphatic sheath (PALS) and periellipsoidal lymphatic sheath (PELS). No lymph nodules and marginal zones were found. The spleen-blood barrier stood in the PELS and the ellipsoid. The high endothelial lining of penic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…Moles, pigs, cats and dogs have numerous and wide ellipsoids, while horses, cows and sheep have medium ellipsoids sizes (Bacha & Bacha, ; Blue & Weiss, ; Press & Landsverk, ; Snook, ). Ellipsoids have a strategic function as filtration of bloodborne pathogen as well as marginal zones (Blue & Weiss, ; Boes & Durham, ; Steiniger, ) and take a role as a major site of blood pathogen filtration in soft‐shelled turtles and chickens that do not possess a marginal zones (Bao, Li, Wang, Qin, & Xu, ; Zhang et al, ). A large number of ellipsoids in the fruit bats indicate that the central arteries branch out many capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Moles, pigs, cats and dogs have numerous and wide ellipsoids, while horses, cows and sheep have medium ellipsoids sizes (Bacha & Bacha, ; Blue & Weiss, ; Press & Landsverk, ; Snook, ). Ellipsoids have a strategic function as filtration of bloodborne pathogen as well as marginal zones (Blue & Weiss, ; Boes & Durham, ; Steiniger, ) and take a role as a major site of blood pathogen filtration in soft‐shelled turtles and chickens that do not possess a marginal zones (Bao, Li, Wang, Qin, & Xu, ; Zhang et al, ). A large number of ellipsoids in the fruit bats indicate that the central arteries branch out many capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the spleen in amphibia is similar to that of fishes, with the exception that reticular cells are present in the follicle areas [67]. The spleens of reptiles [68] exhibit a somewhat more elaborate microanatomical structure, but still lack the canonical germinal centers (GCs) that were first recognizable in the spleen of birds [69]. In the mammalian spleen, a further functional advance seems to be the emergence of a specialized antigen-trapping device, the marginal zone, populated by a certain type of macrophage [70].…”
Section: Reviewmentioning
confidence: 93%
“…They reported that the BSB is composed of splenic sinus endothelial cells, vascular basement membrane, reticular cells, and macrophages. The BSB is a kind of immune barrier, functioning as a mechanical and biological barrier, and presenting antigens to maintain a stable spleen microenvironment ( Bao et al., 2009 ).…”
Section: Introductionmentioning
confidence: 90%